PARADIGMA MULTIKULTURALISME DAN PENGEMBANGAN KURIKULUM PAI - Ahsantudhoni Ahsantudhoni (Institut Keislaman Abdullah Faqih Gresik, 2018)
Muslims should be able to survive and protect minorities. This is where the multiculturalism paradigm becomes important to be integrated in the principles of developing the PAI curriculum so that formal, informal, informal Islamic education institutions can produce healthy multicultural societies and become peace pioneers among religious communities. Subs-tantively, multicultural values are found in several verses of the Qur'an. QS. Ali Imran 3:64 emphasizes dialogue so that the potential for mutual understanding among religious communities is awakened. QS. Al-Hujurat 49:13, contains at least three principles concerning living in diversity and diversity, plural is common, equal is common, modesty in diversity. These verses of the Qur'an become the religious principles of curriculum development.Key Words: Multicultural Paradigm, Islamic Curriculum Development